2018
DOI: 10.3389/fpsyg.2018.01890
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Current Anti-doping Regime – A Quantitative Study Among German Top-Level Cyclists and Track and Field Athletes

Abstract: In recent years anti-doping organizations have implemented various measures to deter elite athletes from using performance-enhancing drugs. One of the main challenges in the fight against doping is that the effectiveness of these anti-doping measures is still unknown. Since the effectiveness of the measures depends primarily on the athletes’ perception, this study focuses on the following four objectives: (1) How effective do top-level athletes perceive individual anti-doping measures to be? (2) Are the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Thirty-nine studies, including 31 research articles, two conference abstracts and six research reports, were selected for inclusion as research on the perceived legitimacy of antidoping organisations and testing. Thirty of these studies utilised quantitative methodology (Al Ghobain, 2019;Donovan et al, 2015;Bourdon et al, 2014; Canadian Centre for Ethics in Sport (CCES), 2013;de Hon, Eijs & Havenga, 2011;Duiven, de Hon & Netherlands ADA, 2015;Dunn et al,2010;Efverstrom et al, 2016a;Gebert, Lamprecht & Stamm, 2017;Global Athlete, 2020;Gucciardi, Jalleh, & Donovan, 2011;Hanstad & Loland, 2009;Hanstad, Skille & Thurnston, 2009;Jalleh, Donovan, & Jobling, 2013;Judge et al, 2010;Moston, Engelberg & Skinner, 2015a;Nolte et al, 2014;Overbye, 2016;Overbye, 2017;Overbye & Wagner, 2013;Overbye & Wagner, 2014;Sas-Nowosielski & Świątkowska, 2007;Scharf, Zurawski & Ruthenberg, 2018;Striegel, Vollkommer & Dickhuth, 2002;USADA, 2017;Valkenburg, de Hon & van Hilvoorde, 2014;Westmattelmann et al, 2018) and nine used a qualitative approach to data collection and analysis (Bloodworth & McNamee, 2010;Efverstrom et al, 2016b;Engelberg, Moston & Skinner, 2015;Erickson, Backhouse & Carless, 2017;Henning & Dimeo, 2018;Kegelaers et al, 2018;Kirby, Moran & Guerin, 2011;…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-nine studies, including 31 research articles, two conference abstracts and six research reports, were selected for inclusion as research on the perceived legitimacy of antidoping organisations and testing. Thirty of these studies utilised quantitative methodology (Al Ghobain, 2019;Donovan et al, 2015;Bourdon et al, 2014; Canadian Centre for Ethics in Sport (CCES), 2013;de Hon, Eijs & Havenga, 2011;Duiven, de Hon & Netherlands ADA, 2015;Dunn et al,2010;Efverstrom et al, 2016a;Gebert, Lamprecht & Stamm, 2017;Global Athlete, 2020;Gucciardi, Jalleh, & Donovan, 2011;Hanstad & Loland, 2009;Hanstad, Skille & Thurnston, 2009;Jalleh, Donovan, & Jobling, 2013;Judge et al, 2010;Moston, Engelberg & Skinner, 2015a;Nolte et al, 2014;Overbye, 2016;Overbye, 2017;Overbye & Wagner, 2013;Overbye & Wagner, 2014;Sas-Nowosielski & Świątkowska, 2007;Scharf, Zurawski & Ruthenberg, 2018;Striegel, Vollkommer & Dickhuth, 2002;USADA, 2017;Valkenburg, de Hon & van Hilvoorde, 2014;Westmattelmann et al, 2018) and nine used a qualitative approach to data collection and analysis (Bloodworth & McNamee, 2010;Efverstrom et al, 2016b;Engelberg, Moston & Skinner, 2015;Erickson, Backhouse & Carless, 2017;Henning & Dimeo, 2018;Kegelaers et al, 2018;Kirby, Moran & Guerin, 2011;…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Treating athletes equally and fairly. Athletes' perceptions of fairness within the anti-doping system was the focus of nine studies included in this review (Al Ghobain, 2019;Donovan et al, 2015;Engelberg et al, 2015;Judge et al, 2010;Qvarfordt et al, 2019;Scharf et al, 2018;Valkenburg et al, 2014;Westmattelmann et al, 2018). These studies were conducted with participants from Australia…”
Section: Justmentioning
confidence: 99%
See 2 more Smart Citations
“…a decreasing wish to use doping in view of the serious consequences 20,21 . Two surveys involving German and Danish elite athletes reported that effective detection methods and hard sanctions are considered to be the main deterrent among the athletic population, indicating that prevention and communication are also important to stop doping abuse 22,23 …”
Section: Introductionmentioning
confidence: 99%